Morphological and structural comparison of TIPS-PEN:PS and neat TIPS-PEN films grown onto cPVP-patterned plastic substrates. (2021) - Grammatikos, S.; Kaimakamis, T.; Panos, S.; Gravalidis, C.; Laskarakis, A.; Logothetidis, S.
Abstract: In the present study, spray-coated blends of 6, 13-Bis(triisopropylsilylethynyl)pentacene (TIPS-PEN) with Polystyrene (PS) insulating polymer were employed to improve the performance of spray-coated neat TIPS-PEN Organic Field-Effect Transistors (OFETs) on plastic substrates. By combining TIPS-PEN with PS insulating polymer, control over the TIPS-PEN crystallization behavior can be achieved. A surface morphology study on the TIPS-PEN blended with PS films at an optimized weight ratio of 0.8:0.2 was carried out, in order to investigate the phase separation phenomena between the two components within the blend. The crystallinity and the crystalline characteristics of the sprayed TIPS-PEN:PS blend films were also investigated and compared to those of the sprayed neat TIPS-PEN films. Finally, these improved characteristics of the blend-based films are correlated with the extracted electrical parameters (mobility value, on/off current ratio, threshold voltage value) of the sprayed TIPS-PEN:PS blend OFETs and are compared with those of the sprayed neat TIPS-PEN OFETs, both in terms of values and inter-device uniformity.